Low-boom low-drag optimization in a multidisciplinary design analysis optimization environment - Sun, Yicheng; Smith, Howard (Elsevier, 2019)
This paper introduces a multidisciplinary design analysis and optimization environment called GENUS. The GENUS aircraft design environment’s key features are that it is modular, expandable, flexible, independent, and sustainable. This paper discusses the application of this environment to the design of supersonic business jets (SSBJs). SSBJs are regarded as the pioneers of the next generation of supersonic airliners. Methodologies appropriate to SSBJs are developed in the GENUS environment. The Mach plane cross-sectional area is calculated based on the parametric geometry model. PANAIR is integrated to perform automated aerodynamic analysis. The drag coefficient is corrected by the Harris wave drag calculation and form factor method. The sonic boom intensity is predicted by the wave form parameter method, which is validated by PCBoom. The Cranfield E-5 SSBJ is chosen as a baseline configuration. Low-boom and low-drag optimization are carried out based on this configuration. Through the optimization, the sonic boom intensity is mitigated by 71.36% and the drag decreases by 20.65%.
Keywords: Multidisciplinary design analysis and optimization (MDAO); Supersonic business jet (SSBJ); Sonic boom